On the contribution of thermal excitation to the total 630.0 nm emissions in the northern cusp ionosphere - Kwagala, Norah Kaggwa; Oksavik, Kjellmar; Lorentzen, Dag Arne; Johnsen, Magnar Gullikstad (Journal of Geophysical Research: Space Physics, 2017)
Source at http://dx.doi.org/10.1002/2016JA023366 Direct impact excitation by precipitating electrons is believed to be the main source of 630.0 nm emissions in the cusp ionosphere. However, this paper investigates a different source, 630.0 emissions caused by thermally excited atomic oxygen O(1D) when high electron temperature prevail in the cusp. On 22 January 2012 and 14 January 2013, the European Incoherent Scatter Scientific Association (EISCAT) radar on Svalbard measured electron temperature enhancements exceeding 3000 K near magnetic noon in the cusp ionosphere over Svalbard. The electron temperature enhancements corresponded to electron density enhancements exceeding 1011 m−3 accompanied by intense 630.0 nm emissions in a field of view common to both the EISCAT Svalbard radar and a meridian scanning photometer. This offered an excellent opportunity to investigate the role of thermally excited O(1D) 630.0 nm emissions in the cusp ionosphere. The thermal component was derived from the EISCAT Radar measurements and compared with optical data. For both events the calculated thermal component had a correlation coefficient greater than 0.8 to the total observed 630.0 nm intensity which contains both thermal and particle impact components. Despite fairly constant solar wind, the calculated thermal component intensity fluctuated possibly due to dayside transients in the aurora.